Desenvolvimento de ações de saúde do trabalhador na atenção primária à saúde: um estudo de caso - Luisa da Matta Machado Fernandes (2012)
Introduction: Among Brazils Public Health System attributions is the Workers Health (WH). Through the years were published laws and documents to built the Workers health National Policy, from which we can emphasize the National System of Global Attention in Workers Health and the Primary Care Guidelines 5, which specifies the attributions, regarding WH, of the professionals who work at the Family Health Team (FHT). Despite all the efforts the WH still has to overcome challenges to be integrated with Brazils Public Health System. One of the strategies used to achieve this gold is to be inserted through the Primary Health Care (PHC), which is today the base for restructuration of the health system in the country. It is possible to affirm that the integration between WH and Brazils Public Health System depends of its assimilation by the PHC. Objective: This study aims to identify the WH actions developed by a FHT from a municipality in Minas Gerais through case study. Method: The research was a qualitative and exploratory case study in a municipality form Minas Gerais. The data were collected trough documents, interviews with key informants and focus groups with the FHT and the Workers Health Center team. The key informants interviewed were municipal Technical Reference in Workers Health, the regional Technical Reference in Workers Health, the Regional Coordinator of PHC and the coordinator of WH Center. The municipality for the study was chosen in two steps: the selection form a Healths Regional and the selection form the city that belongs to the Healths Regional selected. The Healths Regional was chosen through the following criteria: a) has a Technical Reference in Workers Health indicated for two years at least; b) has the support of a Workers Health Center; c) has over 50% of the population covered by the Family Health Program (FHP). Those criterias defined five possible regions, and one of them was selected after interview with the coordinator from the WH in the Health Secretary of Minas Gerais. For the selection of the municipality was used the following criteria: a) has a Technical Reference in Workers Health; b) has over 50% of the population covered by the FHP; c) has notified health problems related to work at the PHC information system. To complement the selection of the municipality were conducted interviews with the Regional Technical Reference in WH, the Regional Coordinator of PHC and the coordinator of WH Center. After, the FHT was indicated by the Municipal Technical Reference in WH. Subsequently was held the characterization of the municipality, through secondary data, and exploratory visit, where documents were collected, which assisted in the characterization, identification of the key informants and the data analysis. Results: The results are presented in three categories: a) Workers health actions in PHC; b) facilitating factors; c) difficulties. We observed that the FHT develops WH actions in daily work, including: mapping of productive activities in the territory, characterizing of users as workers, notification of diseases related to workers health, identification and guidance on risks and dangers work related; home visits and educational activities at companies in the region. Among the facilities found we have: the interaction between FHT and the support team for the family health; the performance of the regional office, the support from the WH Center and the regional technical reference in WH. Among the difficulties we highlight the organization and operation of the PHC, the low priorization of managers, the necessity of instructions to the PHC professionals and the resistance from the workers to access the health service. Conclusion: We observed that the team develops WH actions in consonance with the National Policy for Primary Health Care, identifying what was easy and what was difficult in the process. We conclude on the possibility of developing actions of WH in PHC and recommend the investment in professional qualification and the built of a technical support for the PHC professionals.